Military Operation Other Than War (MOOTW): Military and Civilian Synergy to Support the Citarum River Revitalization Program - et. al., Yusa Djuyandi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the program operations carried out at Region Military Command III (Kodam III) Siliwangi is the management of the Citarum River. Region Military Command III (Kodam III) Siliwangi participated by carrying out cooperation with the regional leadership meeting forum (Muspida) through the task force activities and contributing to handle the Citarum River. Furthermore, this study used qualitative methods, with primary data obtained from observations and interviews with some informants determined purposively.The information came from the military and local government elements, they were determined because the knowledge they have was related to the synergy between the army and civilians in the Citarum River revitalization program. The data that had been obtained is triangulated to determine the validity of the data. Civil-military synergy in the Citarum River Revitalization Program is related to the concept of "Pentahelix", which involves governments, academics, business people, the media and the public, who work together in making changes. The involvement of the army in revitalizing the Citarum River program is quite beneficial, especially related to the socialization and monitoring of river cleanliness.